A Study of Visual–Verbal Relations in Children’s Picture Book "Ibu di Mana?" - Arviana, Roswita Nerrisa; Putri, Kintani (Wimba : Jurnal Komunikasi Visual, 2025)
Children’s picture books are an effective medium to introduce early learning about self-protection in public spaces. This is crucial because such spaces, including markets and shopping centers, while stimulating children’s curiosity, may also pose safety risks. This study aims to examine the visual-verbal relations in the children’s picture book “Ibu di Mana?” (“Where is Mom?”) and to explore how the interplay between text and illustration can support children’s safety literacy. The research employs a descriptive qualitative approach through observation and literature review, analyzed using Ferdinand de Saussure’s semiotic theory and the picture-text relationship framework of Nikolajeva & Scott. The findings indicate that variations in visual-verbal relations create layers of meaning that enrich the narrative and highlight the role of illustrations as both independent conveyors of meaning and complements to the text, underscoring the importance of understanding text-image relations in the design of children’s picture books.